Case Report: A rare case of Noonan syndrome with multiple lentigines manifesting as cardiac enlargement - Linghua Fan; Jie Jiang; Yan Zhang; Xiaoning Han; Wenhui Ding; Xiaodi Xue; Yimeng Jiang (Frontiers in Cardiovascular Medicine)
Noonan syndrome with multiple lentigines (NSML) is a rare autosomal dominant disorder, primarily caused by variants in the PTPN11 gene. Characterized by multiple lentigines, hypertelorism, short stature, and hearing loss, its common cardiac manifestations include pulmonary stenosis, hypertrophic cardiomyopathy (HCM), atrial septal defect, and left-sided heart lesions. We report a 58-year-old female diagnosed with NSML presenting with bilateral atrial and ventricular chamber enlargement and atrial fibrillation, which are uncommon cardiac phenotypes of NSML.